Formation of a transformed follicle is necessary but not sufficient for development of an avian leukosis virus-induced lymphoma. - Baba, T W (1985)
Avian leukosis virus (ALV) infection of susceptible chickens induces bursal lymphomas after a latent period of several months. The clonal development of these B-cell tumors is believed to be a multistep process. Histopathological changes, referred to as transformed follicles, occur within the target organ soon after virus infection and may represent a proximal stage of lymphomagenesis. To establish further the significance of this lesion and its relationship to the subsequent development of lymphomas, we have compared the incidence of transformed follicles observed in animals susceptible or resistant to ALV-induced tumor development. During the 8 weeks following ALV infection, transformed follicles were detected in 82% of the susceptible animals and in 11% of the resistant animals. These results indicate that the incidence of transformed follicles in these animals correlates with their susceptibility to lymphoma development. Furthermore, each transformed follicle does not develop into a tumor. These observations suggest that the formation of a transformed follicle is necessary but not sufficient for lymphoma development.